1992
DOI: 10.1042/bj2880713
|View full text |Cite
|
Sign up to set email alerts
|

A red cell band 3 variant with altered stilbene disulphonate binding is associated with the Diego (Dia) blood group antigen

Abstract: 1. We have shown that the Dia antigen of the Diego blood group system is associated with the presence of red cell band 3 Memphis, but not all band 3 Memphis samples carry the Dia antigen. 2. The band 3 Memphis associated with the Dia antigen was covalently labelled by 4,4'-di-isothiocyanato-1,2-diphenylethane-2,2'-disulphonic acid (H2DIDS) more readily than was normal band 3 or band 3 Memphis not associated with the Dia antigen. This altered reactivity with H2DIDS has previously been noted for a band 3 Memphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The Diego blood (Dia) group antigen was the first to be ascribed to an amino acid change in the extracellular portion of AE1 (Spring, Bruce, Anstee, & Tanner, 1992). As such, these epitopes define regions of AE1 that face the cell exterior, thereby providing valuable topological information ( Fig.…”
Section: Ae1-associated Blood Group Antigensmentioning
confidence: 99%
“…The Diego blood (Dia) group antigen was the first to be ascribed to an amino acid change in the extracellular portion of AE1 (Spring, Bruce, Anstee, & Tanner, 1992). As such, these epitopes define regions of AE1 that face the cell exterior, thereby providing valuable topological information ( Fig.…”
Section: Ae1-associated Blood Group Antigensmentioning
confidence: 99%
“…Membranes were prepared from untreated or chymotrypsin-treated red cells (26). The membrane proteins were separated by SDS-PAGE using the method of Laemmli (27).…”
Section: Anion Transport Studiesmentioning
confidence: 99%
“…Recently, we have shown that the AE-1 variant known as Memphis variant I1 is associated with the expression of the Diego (Dia) blood group antigen (16). Further studies have revealed that the Occurrence of the Dia antigen is dependent upon the AE-1 mutation Pro854 -+ Leu (17).…”
Section: Location Of the Dia Antigen To Ae-1mentioning
confidence: 97%